Arrière-texte et histoire littéraire culturelle - Trouvé, Alain (Verbum – Analecta Neolatina, 2012)
Is literature a cultural product among others? This paper proposes a qualified answer, in association with the notion: "arrière-texte". It is a concept of the nineteen-sixties and a forgotten rival of intertext but has recently been studied again at the University of Reims. The "arrière-texte" accounts for the process of artistic creation from the respective points of view of the author and the reader. Its four aspects — concealed intertext, text–image relation, individual and collective circumstances, desiring body — not only include but also go further than the cultural dimensions. The relation between literature and history, for example, shows that an author can dialogue with historians but that he alone really takes into account the association of desiring subjects with wide-ranging history. In the same way, while it is perfectly conceivable to put words onto images, literature also uses the plasticity of verbal language to let one feel the preverbal affects created by certain images.